Slaying digital dragons : tips and tools for protecting your body, brain, psyche, and thumbs from the digital dark side - Packer, Alex J. (Free Spirit Publishing Inc., 2021)
"This frank and humorous guide helps teens learn how to lead a safe and healthy digital life, join the resistance, and protect themselves from Big Tech's attempted takeover of their brain, body, emotions, privacy, and future"--